Efficacy of Surgery for Internal Snapping Hip - Kroger, E. W.; Griesser, M. J.; Kolovich, G. P.; Ellis, T. J. (International Journal of Sports Medicine, 2013)
Our purpose was to evaluate evidence regarding the effectiveness of open iliopsoas release and lengthening with arthroscopic approaches, which combine iliopsoas release with the treatment of intra-articular pathology as treatments for internal snapping hip syndrome. Searches were performed of 4 databases and 12 reports on the surgical treatment of internal snapping hip were reviewed. The authors tabulated data according to year of study, journal, study type, level of evidence, patient demographics, procedure, and outcomes. We found that surgical treatment of internal snapping hip improves patient symptoms in the majority of patients. Endoscopic release is associated with fewer reported complications compared with open release. All studies of endoscopic treatment of internal snapping hip syndrome also performed intra-articular examination and treatment of intra-articular pathology. The incidence of associated intra-articular pathology was reported in 5 of 6 studies. These results suggest that a painful snapping iliopsoas tendon in many cases may be a result of intra-articular hip pathology rather than an independent entity. Early studies suggest no difference in efficacy or associated complications rate when comparing extracapsular to transcapsular iliopsoas tendon release. Further studies are needed comparing operative to nonoperative treatment and methods of determining patients likely to benefit from operative intervention.
Keywords: snapping hip; internal snapping hip; coxa saltans